Corporate Finance / Third Edition - Jaffe F. Jeffrey; Ross A. Stephen; Westerfield W. Randolph (Irwin Mcgraw-Hill, 1993)
Overview, Introduction to Corporate Finance, Accounting Statements and Cash Flow, Value and Capital Budgeting, Financial Markets and Net Present Value: First Principles of Finance (Advanced), Net Present Value, How to Value Bonds and Stocks, Some Alternative Investment Rules, Practical Application of Capital Budgeting Techniques, Risk, Capital Markets: An Overview, Return and Risk, An Alternative View of Risk and Return: The Arbitrage-Pricing Theory, Risk and Return and Capital Budgeting, Capital Structure and Dividend Policy, Corporate-Financing Decisions and Efficient Capital Markets, Capital Structure: Limits to the Use of Debt, Long-Term Financing, Options and Corporate Finance, Warrants and Convertibles, Leasing, Hedging Risk, Financial Planning and Short-Term Finance, Short-Term Finance and Planning, Credit Management, Special Topics, Mergers and Acquisitions, International Corporate Finance, Glossary, Index.
Overview, Introduction to Corporate Finance, Accounting Statements and Cash Flow, Value and Capital Budgeting, Financial Markets and Net Present Value: First Principles of Finance (Advanced), Net Present Value, How to Value Bonds and Stocks, Some Alternative Investment Rules, Practical Application of Capital Budgeting Techniques, Risk, Capital Markets: An Overview, Return and Risk, An Alternative View of Risk and Return: The Arbitrage-Pricing Theory, Risk and Return and Capital Budgeting, Capital Structure and Dividend Policy, Corporate-Financing Decisions and Efficient Capital Markets, Capital Structure: Limits to the Use of Debt, Long-Term Financing, Options and Corporate Finance, Warrants and Convertibles, Leasing, Hedging Risk, Financial Planning and Short-Term Finance, Short-Term Finance and Planning, Credit Management, Special Topics, Mergers and Acquisitions, International Corporate Finance, Glossary, Index.